2016
DOI: 10.1051/0004-6361/201628855
|View full text |Cite
|
Sign up to set email alerts
|

The SERMON project: 48 new field Blazhko stars and an investigation of modulation-period distribution

Abstract: Aims. We investigated 1234 fundamental mode RR Lyrae stars observed by the All Sky Automated Survey (ASAS) to identify the Blazhko (BL) effect. A sample of 1547 BL stars from the literature was collected to compare the modulation-period distribution with stars newly identified in our sample. Methods. A classical frequency spectra analysis was performed using Period04 software. Data points from each star from the ASAS database were analysed individually to avoid confusion with artificial peaks and aliases. Stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
3
16
1
Order By: Relevance
“…Median and average values of the modulation periods are 59.6 days and 126 days, respectively. The median value is basically the same as what was found by Skarka et al (2016). The distribution of the logarithm of the Blazhko periods is not Gaussian as it is best apparent from the bottom panels of Fig.…”
Section: Modulation Periodssupporting
confidence: 81%
“…Median and average values of the modulation periods are 59.6 days and 126 days, respectively. The median value is basically the same as what was found by Skarka et al (2016). The distribution of the logarithm of the Blazhko periods is not Gaussian as it is best apparent from the bottom panels of Fig.…”
Section: Modulation Periodssupporting
confidence: 81%
“…(i) BL stars -stars with detectable side peak(s) within f0 ± 0.3 c/d, but no closer than 1.5/TS (Nagy & Kovács 2006;Skarka et al 2016). As a BL star we also considered stars that showed unambiguous secular amplitude variations with side peaks indicating modulation period longer than 2/3 TS.…”
Section: Searching For the Bl Effectmentioning
confidence: 99%
“…1. The mean value of the Blazhko periods in M3 is larger than obtained for the inhomogeneous sample of stars by Skarka et al (2016) as can be seen in Fig. 1.…”
Section: Modulation Periodsmentioning
confidence: 61%
“…Collecting a large sample of Blazhko stars (1628 stars) Skarka et al (2016) found that the distribution of the modulation periods is log-normal with log(P mod ) = 1.78(3)±0.30 mean value. The 1σ uncertainty of the mean is given in parenthesis.…”
Section: Modulation Periodsmentioning
confidence: 99%